Effect of cooling distance on DC-LSND treatment on weld defects and weld fractures of A-36 steel - Heri Wibowo; Muhammad Noer Ilman; Priyo Tri Iswanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
Control of weld defects and weld fractures in the welding construction should be done to provide the quality assurance of the welding products and to provide a positive assessment of construction to meet technical and economic requirements. The objective of this study is to investigate the effect of the cooling distance on DC-LSND (dynamic controlled low stress no distortion) treatment on weld defects and weld fractures to obtain the best characteristic of the treatment. In this research, DC-LSND treatment was performed by cooling the both sides near weld line applied in welding process. The cooling media used cryogenic liquid nitrogen sprayed by nozzle. The nozzle was placed at a various distance behind the weld torch. Weld defect was investigated by radiograph test. Tensile strength was tested by servo pulser machine and weld fracture was examined by macro structure and SEM. Results showed that the DC-LSND treatment with a cooling nozzle that is too close to the weld torch has the potential to cause weld imperfections. Porosity and initial welding defect lead to the decrease in the tensile strength of the weld metal and the brittle fracture based on the fracture shape. SEM fractography shows that DC-LSND treatment tends to increase the number of inclusions that have an effect on increasing hardness.